PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK - Muadz Rizki Muzakki; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This study aims to examine the effect of corporate social responsibility (CSR) and capital intensity to tax avoidance. The purpose of this study is to provide empirically evidence about the effect of CSR and capital intensity to tax avoidance. The independent variables of this study are CSR and capital intensity, the dependent variable is tax avoidance, and control variables are size and  profitability.  CSR  measured by  CSR  disclosure with  GRI  G3.1 as  the  indicator.  Capital intensity measured by total fixed asset divide by total asset. Size measured by logarithm of total asset. Profitability measured by Return on Asset (ROA). Tax avoidance measured by effective tax rates (ETR).The population in this study are 446 manufacturing companies which listed on Indonesian Stock Exchange in the period of 2011-2013. Sample were selected by purposive random sampling method and finally obtained 211 manufacturing companies that fulfill the criteria. Data were analyzed using multiple regression analysis model.The result show that CSR and capital intensity significant negatively influence tax avoidance. Based on the result, conclude that tax avoidance decision is influenced by its attitude about CSR and capital intensity.